Effect of Potassium on Potato Tuber Production in Acid Soils of Malepatan, Pokhara - Adhikari, BH; Karki, KB (Nepal Agriculture Research Journal, 2009)
Soils of Pokhara valley, especially Malepatan, are fine textured silt loam, extremely acidic in nature (3.7-4.0 pH) and are medium in soil potassium content. On-station experiments were conducted to assess the response of potassium (K2O) and its application methods on potato tuber yield in an extremely acid soil condition. Six potassium levels (0, 50, 75, 100 kg ha-1 as basal application, 50 kg basal plus 50 kg top dressed, and 50 kg basal plus 50 kg foliar application) were tested in the experiment for three consecutive years (2000, 2001 and 2002). A randomized complete block design (RCBD) with 3 replications was employed. Variety used was MS 42. Nitrogen (N), phosphorus (P2O5) and compost were applied as basal dose in each plots at the rate of 100 kg, 50 kg and 20 t ha-1, respectively. Three years mean result on the plant growth characters revealed that tallest plant height was recorded (33.22 cm) when 50 kg ha-1 potassium was applied basally and 50 kg ha-1 top-dressed. The trend was quite similar in tillers production (6.96 branches plant-1) and biomass production (168.66 g plant-1). Maximum of 473.33-g plant-1 of tubers was produced when 100 kg of potassium was applied basal single dose. Highest tuber yield of 24.75 t ha-1 of tuber were produced when 50 kg potassium was applied basally and 50 kg top- dressed, a total of 100 kg ha-1. Highly significant response of potassium levels on tuber production was observed in all the years. The results of this investigation suggested that application of potassium (K2O) at the rate of 50 kg ha-1 basal and 50 kg ha-1 top-dressed in 45 days could increase potato tuber yield satisfactorily in extremely acid soil condition. Key words: Basal application; potassium levels; Solanum tuberosum; tuber production; topdressing DOI: 10.3126/narj.v7i0.1867 Nepal Agriculture Research Journal Vol.7 2006 pp.42-48